The contribution of adaptive selling to positive word-of-mouth in Malaysian computer retail business - Wan Omar, Maznah; Jusoff, Kamaruzaman; Mohd Ali, Mohd Noor (2009)
The application of salesperson adaptive selling skills and sales presentation skills by a salesperson during their interaction with customers in the sales situation can have a significant effect on customer intention to promote through word-of-mouth in the Malaysian Computer retail business. The purpose of this paper is to examine the relations between salesperson adaptive selling skills, positive word-of-mouth and the relative roles played by cognitive satisfaction in the development of customer satisfaction which will lead to customer’s intention to promote through word-of-mouth in a computer retail setting in Malaysia. This will then lead to increased benefits for the organization in the form of customer loyalty. The cognitive evaluation of customer satisfaction was found to explain customer loyalty in a retail setting significantly. This finding holds importance to those retailers who have been able to generate high expectations in the eyes of their customers.